Кластерне дослідження дефіциту йоду та ефективності масової йодної профілактики в Чернігівській області - Осадців, О. І.; Кравченко, В. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
The authors have conducted for the first time a study of iodine status of the population of all districts of Chernigiv region. The median of ioduria in certain districts was within the range 45.75 to 119.09 mcg/L. For the region as a whole, a mild degree of iodine deficiency has been reported in the presence of an ioduria median of 80.08 mcg/L. Epidemiological investigations have shown a high level of frequency of goiter cases among children: from 13.3% to 83.3%; for the region this index averaged 48.2%. The impact of nutrition structure on iodine status of children has been studied. Iodized salt is to be considered an essential additional source of iodine: according to the results of a survey, 52.3% of children periodically consumed iodized salt, 29.7% consumed sea-food, and only 2.6% were taking iodine-containing preparations. The climatic and geographical area of residence had no impact on iodine status of children; the presence of mass iodine prophylaxis played an essential role in the region under study. A significant difference has been found between ioduria indices of urban and rural residents. Introduction of a mass iodine prophylaxis using iodized salt is recommended.